Bioinspired Hybrid White Light‐Emitting Diodes. (13th August 2015) - Weber, Michael D.; Niklaus, Lukas; Pröschel, Marlene; Coto, Pedro B.; Sonnewald, Uwe; Costa, Rubén D.
<x xml:space="preserve">Abstract</x> The first bioinspired hybrid white‐light‐emitting diodes (bio‐HLEDs) featuring protein cascade coatings are presented. For easy fabrication a new strategy to stabilize proteins in rubber‐like material was developed. The synergy between the excellent features of fluorescent proteins and the easily processed rubber produces bio‐HLEDs with less than 10% loss in luminous efficiency over 100 hours.